Neutron scattering and praseodymium suppression of superconductivity - A., L; Longmore, Andrew (1995)
﻿ PrBa2Cu3O6+x is anomalous among the compounds which can be made by substituting different rare-earth ions for yttrium (Y) in YBa2Cu3O6+x:it is the only compound which has the same structure as YBa2Cu3O6+x, and yet does not superconduct. This unusual property makes it an important system to study, since the differences between the two compounds could produce theoretical insights into the mechanisms of cuprate, or high-temperature, superconductivity. This thesis describes neutron scattering investigations of the magnetic properties of PrBa2Cu3O6+x. I have investigated the magnetic ordering in well-characterised, single-crystal samples, both with and without Al-contamination. In the data analysis, proper account is taken of the sample mosaicity and the different intrinsic peak shapes encountered. Some of the most striking new characteristics reported here are that (i), there is a clear interaction between the Pr ions and the Cu-O2 planes, (ii), the ordered Pr moments tilt away from the c-axis (as suggested previously by Mossbauer spectroscopy), and (iii), there is two-dimensional ordering in the Al-containing crystals. I show how observed trends in the magnetic ordering, as O- and Al-contents vary, may be understood in terms of charge redistribution involving the hybridisation of the Pr ions. I have also examined the crystal field transitions of the praseodymium ion. Because of the difficulties previously encountered in measuring these in PrBa2Cu3O6+x, I have used instead the compounds PrO2 and Y0.3Pr0.7Ba2Cu4O8, which contain praseodymium in a chemically similar environment. Y0.3Pr0.7Ba2Cu4O8 shows the same broadening effects as PrBa2Cu3O6+x; PrO2 shows signs of mixed-valency, with temperature-dependent lifetime effects. The application of symmetry considerations and the point-charge model to the crystal field measurements is considered in some detail.